P‐164: Low reflectivity Material Development for Border‐less LCD Product. Issue 1 (29th May 2019) - Zhang, Xiaoxiang; Song, Yongzhi; Ding, Xiangqian; Fu, Fangbin; Jia, Yihe; Han, Hao; Chen, Weitao
Abstract : Low reflectivity material for border‐less LCD product was studied in this paper, and the design of reflectivity structure was also given. For composite film material, an a‐Si/SiNx two‐layer structure can reduce reflectivity by control its' thickness. Experiment result shows that reflectivity drops from 17.59% to 13.53% when a‐Si thickness downs from 350 Å to 150 Å, both samples have a 800 Å thickness of SiNx. MoOx mono‐film was also researched and the reflectivity could be reduced to about 5% at green light wave band. Metal layer on MoOx film influents reflectivity on long‐wave spectrum considerably, samples with Mo/Al/Mo layer have a low reflectivity on full‐/wave band and a black appearance, while the ones with Cu layer have a rising reflectivity on long‐wave band and a dark red color. Furthermore, the reflectivity of doping Ta was studied in MoOx. Ta could adjust the reflectivity of MoOx, and 6% of the doping ratio is the best.